PENGARUH KEPERCAYAAN PASIEN DAN LINGKUNGAN FISIK PUSKESMAS TERHADAP MINAT KUNJUNGAN ULANG PASIEN DENGAN PATIENT ENGAGEMENT SEBAGAI MEDIASI DI PUSKESMAS “X” KOTA JAMBI - Titania Az Zahra; Purwadhi, Purwadhi; Kahar Mulyani (Journal of Innovation Research and Knowledge, 2025)
A common issue faced by Puskesmas is the low rate of patient revisit intention, which can impact the quality of healthcare services. One of the factors that may influence this issue is patient trust in the services provided, as well as the physical environment of the Puskesmas, which can create comfort for patients. However, few studies have examined the relationship between patient trust and the physical environment of Puskesmas with revisit intention, especially with patient engagement as a mediating factor. This study aims to examine the influence of patient trust and the physical environment of Puskesmas on patient revisit intention, with patient engagement as a mediator, at Puskesmas “X” , Jambi City. This quantitative study uses a survey design and purposive sampling of 100 patients who have received services at the Puskesmas. Data were collected using questionnaires measured with a Likert scale and analyzed using Structural Equation Modeling (SEM). The results of the study show that patient trust has a positive and significant effect on patient engagement, which in turn influences patient revisit intention. Furthermore, the physical environment of the Puskesmas also has a direct influence on patient engagement and revisit intention. Patient engagement serves as a mediator that links the influence of patient trust and the physical environment of Puskesmas on patient revisit intention. These findings indicate the importance of managing patient trust and the physical environment to enhance patient involvement and their intention to revisit the Puskesmas. This study contributes to policies for improving the quality of healthcare services at Puskesmas to increase patient satisfaction and revisit intention